Cross-cultural Communication Competency Among Managers: A Study of Organizations in Malaysia. - Norizzati, Azudin (2019)
urpose: This study aims to highlight the necessary competencies among the middle level managers, especially the cross-cultural communication competency. This study was designed to investigate the cross-cultural communication competencies in organizations through the focus group conducted among the senior management levels. Methodology: This study applied the beauty of qualitative research by conducting a focus group of ten participants, where all of them were from various industries in Malaysia. They are well mixed of women and men Senior Managers level and above, where the minimum level of them was the Director, General Manager, and Vice President of private enterprises. Data from the focus group discussion was analyzed and presented in the findings in this article. Results: The findings of this paper proven the need of cross-cultural communication competency currently in Malaysia through the ten (10) participants involved in the focus group research and ten (10) cases were presented in this article. Different participant provided different findings however, the data summarization was presented in the table in results. Majority concluded that employees nowadays are conscious competence and agreed that cross-cultural communication is the most crucial competency needed by all organization today. Implications: This should provide several ideas to the senior management levels in incorporating this aspect into their management training programmes or other activities in all organizations. Further studies could be expanded through the methodology used. Novelty of Study: As past research concentrated more on the leadership and other management competencies, this study was looking at the specific issue of cross-cultural communication competencies among these employees in organizations. With the peculiar scenario